Immunohistochemical characteristics of endometrium hyperplasia in comparison with secretory endometrium - Khaskhachikh , D.A.; Potapov , V.O.; Poslavska , O.V. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. Endometrial hyperplasia (HE) is a pathological increase in the number of cells of the endometrial epithelium, which, in the case of atypical proliferation, is considered a precancerous condition and leads to the development of endometrial carcinoma. The method of immunohistochemically staining plays a significant role in the differential diagnosis of GE without/with atypia and carcinomas. Objective. The aim of this work is the comparative characterization of the expression of immunohistochemically markers in three types of endometrium: endometrial hyperplasia without atypia, endometrial hyperplasia with atypia and secretory endometrium, in order to determine the most informative markers that can serve as diagnostic supplements and prognostic indicators for the transition from endometrial hyperplasia to carcinoma. Methods. The study was performed on endometrial biopsy material from 23 women of reproductive age with abnormal uterine bleeding by curettage, who were diagnosed with GE without/with atypia, 7 women made up the control group with endometrial secretory changes. The expression of progesterone (PR) and estrogen (ER) receptors, as well as p21, dcl-2, KI-67, eNOS, cyclin D1, BAX, b-catenin, E-cadherin and Caspase 3 markers were compared in order to determine the most informative markers that can serve as diagnostic adjuncts and prognostic indicators for the transition from GE to carcinoma. Results. The obtained results indicate a difference in the expression levels of immunohistochemically markers in different types of endometrium. These results are important for further research into the mechanisms of endometrial hyperplasia development and may indicate potential therapeutic targets for the selection of treatment strategies for different types of hyperplasia. Conclusion. The difference between the group of hyperplasia without atypia and the control group of secretory endometrium in the glandular component was demonstrated by markers ER, PgR, b-catenin, p21, cyclin D1, Ki-67, Caspasa-3 (all p<0.05); and in the stromal component - ER, PgR, b-catenin (all p<0.05), which gives reason to use them as the main diagnostic markers. The difference between the group of hyperplasia with atypia and the control group of the secretory endometrium in the glandular component was demonstrated by markers ER, b-catenin, p21, cyclin D1, Ki-67, eNOS (all p<0.05); and in the stromal component - ER, b-catenin and eNOS (all p<0.05), which gives reason to use them as the main diagnostic markers. The difference between the group of hyperplasia without atypia and the group of hyperplasia with atypia in the glandular component was demonstrated by markers PgR, Ki-67, Caspasa-3 eNOS (all p<0.05); and in the stromal component - eNOS (p<0.05), which gives reason to use them as the main diagnostic and prognostic markers. Bcl-2 and BAX markers did not show a statistically significant difference in the study groups, which indicates the impossibility of using them separately as diagnostic or prognostic markers for endometrial hyperplastic processes, and the interpretation of the expression results of these markers must be taken into account in combination with other indicators.